2014
DOI: 10.4238/2014.may.23.9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity screening of wild plant extracts from Saudi Arabia on human breast adenocarcinoma cells

Abstract: ABSTRACT. This study investigated the in vitro anticancer activities of a total of 14 wild angiosperms collected in Saudi Arabia. The cytotoxic activity of each extract was assessed against human breast adenocarcinoma (MCF-7) cell lines by using the MTT assay. Among the plants screened, the potential cytotoxic activity exhibited by the extract of Lavandula dentata (Lamiaceae) was identified, and we analyzed its anticancer potential by testing antiproliferative and apoptotic activity. Our results clearly show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…In this study, the methanolic leaf extract of M. pseudolavatera Webb & Berthel. was examined for its anti-proliferative and pro-apoptotic effects on AML cell lines since leaves from other Malva species have shown cytotoxic effects on other cancer types [12][13][14]. In a previous study by Solowey et al (2014), the ethanolic extract from Urtica membranacea showed potent anti-cancer effects at 750 µg/mL and 1500 µg/mL and these concentrations showed to be therapeutically correlated to a mouse breast cancer model with no side-effects [29].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the methanolic leaf extract of M. pseudolavatera Webb & Berthel. was examined for its anti-proliferative and pro-apoptotic effects on AML cell lines since leaves from other Malva species have shown cytotoxic effects on other cancer types [12][13][14]. In a previous study by Solowey et al (2014), the ethanolic extract from Urtica membranacea showed potent anti-cancer effects at 750 µg/mL and 1500 µg/mL and these concentrations showed to be therapeutically correlated to a mouse breast cancer model with no side-effects [29].…”
Section: Discussionmentioning
confidence: 99%
“…Natural products possess immense pharmacological significance in the development of drugs including cancer (Kuete et al, 2013;Alil et al, 2014). Natural products with potential bioactivity compounds have received major attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The plants screened in this this study (or plants of the same genus) have been previously reported to cause cytotoxic effects towards tumour cells and constitute therefore interesting candidates in a plant bioprospecting program for anticancer activity. The extract of L. dentata possess cytotoxic and pro-apoptotic properties assessed against human breast adenocarcinoma (MCF-7) cell lines using the MTT assay (Ali et al 2014). Ku et al (2014) evaluated antioxidant, antihyperglycemic, anti-cancer, anti-inflammatory, and anti-coagulant activities of hyperoside, an active compound from the genera of Crataegus and Hypericum.…”
Section: Antiproliferative Propertiesmentioning
confidence: 99%